Helge Grell in memoriam - Schjørring, Jens Holger (Grundtvig-studier, 2000)
In Memory of Helge Grell, 1925 - 2000 By Jens Holger Schjørring Helge Grell’s life coincided with some decisive events in the history of research on Grundtvig and Grundtvig’s importance in theology and in the religious and national life in Denmark.When Grell took holy orders in 1940, the year of the occupation of the country by the German Wehrmacht, the depression and confusion over the loss of national independence led many Danes to search for a mobilization of new resources in the Danish people to avoid an internal breakdown. This found expression for example through De danske Ungdomsforeninger (Danish Youth Associations), a particular manifestation being Hal Koch’s famous lectures on Grundtvig and his work for Dansk Ungdomssamvirke (Federation of Danish Youth Associations). In the post-war years the discussion turning on Kaj Thaning’s interpretation of Grundtvig was the point of departure for much debate on the Grundtvigian heritage and in a wider sense the situation of the Danish national church. There was, in particular, Thaning’s protest against tendencies to allow a »pilgrim myth« to determine the understanding of the relationship between created human life and Christianity. Against this Thaning would stress the intrinsic value of created life with his programmatic emphasis on » Man first...«.The last decades of the twentieth century saw, with increasing strength, endeavours being made to apply an international perspective to the interpretation of Grundtvig.Helge Grell lived through all these phases, briefly outlined above, and each one of them came to determine in different ways his work as clergyman, as teacher in many different contexts, as lecturer in Grundtvig circles and participant in their activities, and as Grundtvig scholar. When Helge Grell’s life is considered within such an extensive framework, it becomes apparent that his many activities share an inner coherence. In retrospect, one senses an arch spanning the different aspects of his lifework and combining his practical activity with his work as a Grundtvig scholar. Likewise, when viewed in that light, there is an impressive unity in the books that Grell managed to finish in the last decades of his life, dealing partly with the relation between creator spirit and the spirit of the people, partly with Grundtvig’s travels to England and their significance, and finally with Grundtvig’s folk high school ideas and their realization after Grundtvig’s death.